Facts, norms, and dignity. Issue 1 (2nd January 2019) - Gilabert, Pablo
Abstract: There are three ways in which descriptive claims stating non-normative facts might bear on normative claims such as principles of social justice and human rights. They may identify (a) specific occasions that trigger application, (b) conditions of feasible implementation, and (c) certain sources of value. The first relation is obvious but important: norms cannot be applied without stating circumstances that make their application relevant. The second relation is also important, as norms that cannot be fulfilled are deficient for guiding social practices and institutional design. The first relation is widely accepted and discussed, and I will not say much about it here. I will say more about the second relation, but not much more because I have discussed it in detail in my writings on feasibility. In this paper, my main focus is on the third relation, which remains underexplored in the relevant literature. After identifying the three relations between facts and norms as they arise in recent discussions in political philosophy, I offer an account of their significance by articulating a specific view that I call 'dignitarianism'. According to dignitarianism, at least some of the central norms concerning the treatment of an entity depend on the inherent dignity of that entity. Human rights offer a paradigmatic case of dignitarianism, and I concentrate on them to explore the relations between facts, norms, and dignity.